2009
DOI: 10.1063/1.3276283
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive physical mechanism of two-headed biomotor myosin V

Abstract: Two-headed biomotor myosin V autonomously coordinates its two identical heads in fuel consumption and mechanical stepping, so that the dimerized motor as a whole gains the capability of processive, unidirectional movement along cytoskeletal filament. How the dimer-level functions like sustained direction rectification and autonomous coordination emerge out of physical principles poses an outstanding question pertinent to motor protein biology as well as the nascent field of bioinspired nanomotors. Here the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…The large persistence length l p of the lever arms (26)(27)(28) allows us to propose a coarse-grained polymer model for the reaction-diffusion problem, which, in turn, yields approximate analytical expressions for all the physical observables, including binding times, run length, velocity, and stall force. We have built on the insights of earlier theoretical works (28)(29)(30)(31)(32)(33)(34), which focused on modeling a reaction network of discrete states in the mechanochemical cycle of the motor heads. Our work supplements the reaction network with an explicit treatment of the diffusive search, which has been studied using insightful Brownian dynamics simulations of forward stepping in MyoV (35).…”
mentioning
confidence: 99%
“…The large persistence length l p of the lever arms (26)(27)(28) allows us to propose a coarse-grained polymer model for the reaction-diffusion problem, which, in turn, yields approximate analytical expressions for all the physical observables, including binding times, run length, velocity, and stall force. We have built on the insights of earlier theoretical works (28)(29)(30)(31)(32)(33)(34), which focused on modeling a reaction network of discrete states in the mechanochemical cycle of the motor heads. Our work supplements the reaction network with an explicit treatment of the diffusive search, which has been studied using insightful Brownian dynamics simulations of forward stepping in MyoV (35).…”
mentioning
confidence: 99%
“…Here we only model the first ADP state (with moderate affinity for actin and strong affinity for ADP) while the second one (with strong affinity for actin and weak affinity for ADP) is combined with the A‐M state due to their structural similarity 35. A third ADP state of myosin V with the actin‐binding cleft partially closed and the lever arm in the pre‐powerstroke position was proposed based on kinetic studies21, 24 and theoretical modeling 102, 123. Such ADP state was needed to interpret the EM finding of two‐head‐bound myosin V conformations with the lead‐head lever arm in the pre‐powerstroke position 100, 101.…”
Section: Resultsmentioning
confidence: 99%
“…These studies revealed physical mechanisms 41,45 by which a local conformational change may be amplified into a long-range bias for diffusive binding and by which a sustained directional movement in hand-over-hand gait may be further facilitated for a homodimeric walker. A generalization found a variation of the same mechanism in another biomotor myosin V, 44 and identified a reduced version that may be implemented in engineered systems. 45 Experimental development along this line has yet to come.…”
Section: Two Routes Toward Advanced Artificial Walkersmentioning
confidence: 99%
“…One example is a series of theoretical developments [37][38][39][40] for a rectification mechanism suitable for inchworm walkers. Another example is a group of theoretical studies [41][42][43][44][45] that explored a bio-inspired mechanism for directional rectification in homodimeric walkers.…”
Section: Status Quo Of Research On Artificial Molecular Walkersmentioning
confidence: 99%
See 1 more Smart Citation